Clinical Status of Furosemide on Liver Cirrhosis with Portal Hypertension and Ascites - Thapaliya, K; Bhandary, A; Basnet, S; Aryal, Bijay (Journal of Chitwan Medical College, 2013)
Cirrhosis of liver is a pathologically defined entity that is associated with a spectrum of characteristic clinical manifestations. Portal hypertension is one of the complication of cirrhosis of liver. We report the case of a 55-year-old man with liver cirrhosis and subsequently portal hypertension and ascites who was admitted to the hospital with headache and indigestion. The patient was treated with furosemide 40 mg OD, lactulose 10 ml HS, Tone, vit K 10 gm IV, Usoliv 300 mg BD and pantoprazole 40 mg OD. The relevant and evidence based clinical practice guidelines and clinical status of furosemide on particular condition were discussed with treating physician. Journal of Chitwan Medical College 2013; 3(1): 65-66 DOI: http://dx.doi.org/10.3126/jcmc.v3i1.8470